Profile of a saint: the amazing life of Baray Bhaiyya, Fakhrul Muhaddeseen Maulana Abdul Ghafoor - Wahhab, Abdul (Ziaul Haq Qutubuddin, 2009)
Maulana Abdul Ghafoor, 1905-1985, Islamic scholar from Bangladesh